PREVENTION OF COVID-19 IN PREGNANT MOTHERS: PREVENTION OF COVID-19 IN PREGNANT MOTHERS - Mayusef Sukmana; Anik Puji Rahayu; Alma Fardania Zulfa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Widya Gama Mahakam Samarinda, 2022)
The Covid-19 pandemic has had an impact on maternal and child health services, such asoptimal monitoring of maternal and child health. Offline maternity class services alsoencountered problems and resulted in a lack of information to pregnant women during theCovid-19 pandemic situation. Thus, re-implementing this online class for pregnant womencan reduce misconceptions that are still wrong in everyday life. The method used is an onlinemethod by forming discussion and consultation forums involving pregnant women, posyanducadres, health center midwives. The parameter for achieving this class of pregnant women isthat pregnant women can know how to prevent Covid-19 during pregnancy by applying theuse of adaptation of new habits and applying health protocols in daily life. The purpose of theclass for pregnant women is to increase the knowledge of pregnant women about problemsduring pregnancy and the formation of discussion and consultation forums regarding theprevention of Covid-19 during pregnancy.Keyword: pregnant women, covid-19, health mother